Linking Transitions to Sustainability: Individual Agency, Normativity and Transdisciplinary Collaborations in Transition Management - Niko Schäpke (Leuphana Universität, 2018)
Sustainability transitions research proposes fundamental changes of societal systems' organization to overcome persistent societal challenges, such as climate change or biodiversity loss, and allowing systems to become more sustainable. This thesis addresses an underlying tension in sustainability transitions research: between transitions as an open-ended process of fundamental change and the normative direction of this change: sustainability. In doing so, three themes so far under-explored in sustainability transitions scholarship are in the focus of the research: individual agency, normativity and transdisciplinary collaboration. Thereby, the thesis aims to strengthen process-oriented and potentially transformative approaches to sustainability transition research, in contrast to primarily descriptive-analitical approaches. Transition management as a recent and salient example of transdisciplinary transition research is chosen to provide both, research framework and application context. Based on conceptual-theoretic, empirical case study and reflexive work, three main results are contributed: First, a psychologically enriched understanding of individual and sustainability related agency in conceptual and empirical understandings of transition management is developed. This builds on two perspectives: a psychologically enriched capability approach as well as the analysis of social effects (social learning, empowerment and social capital development) of transition management to capture sustainability oriented agency increases. As second main result, normative considerations, namely sustainability, are included into transition management on conceptual and empirical levels. Therein, substantive, procedural and intentional aspects of sustainability are combined: Substantive aspects are covered by proposing capabilities, behavioral freedoms to live a valuable life, as normative yardsticks to measure developments. Procedural aspects include a detailed understanding of facilitating a learning journey towards making sustainability meaningful in the local transition management cases and setting up experiments for its realization. Intentional aspects are addressed by linking social effects of transition management to awareness, motivations and feelings of responsibility towards sustainability. As a third main result, the transdisciplinary collaboration in transition management of creating an arena as an interactive learning space is conceptualized and explored, as well as the roles of the researchers therein. Key issues of this learning space, the community arena, are drawn out and ideal-type roles and activities of researchers in addressing these issues are proposed and empirically analyzed. As overall synthesis of results, ten principles of sustainability transition management are proposed. – – Forschung zu Nachhaltigkeitstransitionen schlägt einen grundlegenden Wandel der Organisation gesellschaftlicher Systeme vor, um persistenten, andauernden gesellschaftliche Herausforderungen wie Klimawandel und Biodiversitätsverlust zu begegnen und die gesellschaftlichen Systeme nachhaltiger zu gestalten. Die vorliegende Arbeit adressiert eine grundlegende Spannung in der Forschung zu Nachhaltigkeitstransitionen: zwischen einer Transition, als grundlegendem, ergebnisoffenen Wandel und der normativen Zielsetzung dieses Wandels, der Nachhaltigkeit. Dabei sind drei Themen im Fokus, welche bisher wenig Beachtung in der Forschung zu Nachhaltigkeitstransitionen bekommen haben: individuelles Handeln ('Agency'), Normativität und transdisziplinäre Zusammenarbeit. Die Arbeit darauf ab, prozess-orientierte und potentiell transformative Ansätze der Forschung zu Nachhaltigkeitstransitionen, im Gegensatz zu vermehrt deskriptiv-analytischen Ansätzen, zu stärken. Transition Management als aktuelles, populäres Beispiel der transdisziplinären Transition-forschung wird als Forschungsrahmen und Anwendungskontext genutzt. Basierend auf konzeptionell-theoretischer Arbeit, empirischer Fallstudien und kritischer Reflektion werden drei Hauptergebnisse beigetragen: Zuerst wird ein psychologisch vertieftes Verständnis individueller und nachhaltigskeits-bezogener Handlung in Transition Management konzipiert und empirisch untersucht. Dieses fußt auf zwei Perspektiven: einem psychologisch angereicherten Fähigkeiten-Ansatz ('Capability Approach') ebenso wie der Analyse der sozialen Effekte von Transition Management (soziales Lernen, Empowerment/ Befähigung und Sozialkapitalentwicklung) zur Erfassung von nachhaltigkeitsbezogenen Erweiterungen von Handlungsspielräumen. Als zweites Kernergebnis werden normative Überlegungen, namentlich Nachhaltigkeit, in Transition Management auf konzeptioneller und empirischer Ebene einbezogen. Dabei werden substantielle, prozedurale und intentionale Aspekte von Nachhaltigkeit kombiniert: zur Erfassung substantieller Aspekte werden 'Capability'-Erhebungen als normative Messlatte von Entwicklungen vorgeschlagen. Prozedurale Aspekte beinhalten ein detailliertes Verständnis der Gestaltung einer "Lernreise" um Nachhaltigkeit in den Fallstudien vor Ort eine Bedeutung zu verleihen und ihrer Umsetzung über Experimente näher zu kommen. Intentionale Aspekte werden adressiert durch Verbindung der sozialen Effekte von Transition Management mit Aspekten des Nachhaltigkeits-Bewusstseins, der Motivation und der gefühlten Verantwortung für Nachhaltigkeit. Drittes Kernergebnis ist die Konzeptionierung und Erprobung der transdisziplinären Zusammenarbeit in Transition Management in Form der Schaffung einer Arena - eines interaktiven Lernraumes - sowie der Rollen der Forschenden dabei. Kernthemen der Gestaltung dieses Lernraumes, der 'Community Arena', werden herausgearbeitet sowie idealtypische Rollen und Aktivitäten der Forschenden zur Adressierung dieser Themen werden vorgeschlagen und analysiert. Als finale Synthese der Ergebnisse werden zehn Prinzipien des Managements von Nachhaltigkeitstransitionen ('Sustainability Transition Management') vorgeschlagen.
Additional information: PhD Thesis, published as IETSR Discussion Paper No. 2/2018
Keywords: 650; Transdisciplinarity; Sustainability Transitions; Agency; Transition Management; Normativity; Social Learning; Capability Approach; Empowerment